A clinical case of idiopathic pulmonary fibrosis against the background of comorbid pathology - A. V. Teteneva; V. V. Kalyuzhin; G. M. Chernyavskaya; I. D. Bespalova; G. E. Chernogoryuk; V. D. Zavadovskaya; T. V. Zhogina; E. A. Ustyuzhanina; E. V. Kuzin; I. A. Varfolomeeva; O. V. Sedlyar; E. A. Medikova; et al. (Бюллетень сибирской медицины)
Idiopathic pulmonary fibrosis (IPF) is one of the most common diseases in the group of interstitial lung diseases, which is characterized by persistent progression and poor prognosis. Over the past decade, experts have made significant progress in developing a diagnostic algorithm for IPF patients. This algorithm includes analysis of clinical, laboratory, and instrumental data, primarily the results of high-resolution computed tomography (HRCT). Precise adherence to the diagnostic algorithm and correct interpretation of HRCT data are prerequisites for IPF diagnosis.Specialists of the Tomsk region have developed routing of patients with suspected IPF. The presented clinical case is a successful example of adhering to this algorithm. Wide implementation of modern diagnostic algorithms into diagnosis and treatment of IPF and quality improvement of imaging methods, primarily HRCT, carried out as a part of the differential diagnosis, open up prospects for early diagnosis of this pathology. A timely prescribed antifibrotic therapy (nintedanib, pirfenidone) in IPF allows to slow down pathological progression and improves the prognosis.